Engineered Hybrid Vesicles and Cellular Internalization in Mammary Cancer Cells - Kim, So Yun; Guk, Dagyeong; Jeong, Youngdo; Kim, Eunji; Kim, Hansol; Kim, Sung Tae (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Extracellular vesicles play an important role in intercellular communication, with the potential to serve as biomaterials for nanocarriers. Combining such extracellular vesicles and liposomes results in advanced drug delivery carriers. In this study, we attempted to fabricate hybrid vesicles using a membrane fusion method and incorporated an anticancer drug. As a result, we successfully prepared nanosized uniform hybrid vesicles and evaluated their physicochemical characteristics and intracellular uptake mechanisms via endocytosis in various cell lines. Compared to liposomes, the hybrid vesicles showed better physical properties and a relatively higher reduction in cell viability, which was presumably dependent on the specific cell type. These findings suggest that fusion-based hybrid vesicles offer a novel strategy for delivering therapeutic agents and provide insights into the types of extracellular vesicles that are useful in fabricating hybrid vesicles to develop an advanced drug delivery system.